1998
DOI: 10.1203/00006450-199811000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Diodes: A Novel Light Source for Phototherapy

Abstract: High intensity light-emitting diodes (LEDs) are being studied as possible light sources for the phototherapy of hyperbilirubinemic neonates. These power-efficient, low heat-producing light sources have the potential to deliver high intensity light of narrow wavelength band in the blue-green portion of the visible light spectrum, which overlaps the absorption spectrum of bilirubin (BR). We compared the efficacy between single LEDs of different color and then constructed a prototype phototherapy device using 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 16 publications
1
83
0
4
Order By: Relevance
“…Although this difference did not reach statistical significance, the lower efficacy of blue-green phototherapy is consistent with our recent in vitro observations. 11 We compared the in vitro efficacy of LEDs and found that blue light was the most effective in degrading bilirubin by 28% of dark control, followed by blue-green (18% of control), and then white light (14% of control). Green light was the least effective (11% of control).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this difference did not reach statistical significance, the lower efficacy of blue-green phototherapy is consistent with our recent in vitro observations. 11 We compared the in vitro efficacy of LEDs and found that blue light was the most effective in degrading bilirubin by 28% of dark control, followed by blue-green (18% of control), and then white light (14% of control). Green light was the least effective (11% of control).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was decided to compare blue-green LEDs, rather than green LEDs, to blue LEDs and conventional halogen-quartz lamps, in accordance with our previous in vitro efficacy studies. 11 Furthermore, Donzelli et al 9 presented preliminary data suggesting that a unique narrow-spectrum blue-green fluorescent lamp with a peak emission at 480 nm was more effective than Special Blue lamps. The high phototherapeutic efficiency of blue-green light was attributed to the combined effects of the increase from blue to green of the quantum yield, of lumirubin, responsible for the quickest pigment clearance in newborns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that tin protoporphyrin and other metalloporphyrins are not only differential inhibitors of HO-1 and HO-2 (Vreman et al, 1998), but have also been reported to inhibit the activity of cytochrome P450s, nitric oxide synthase, soluble guanylate cyclase, and others (Appleton et al, 1999;Grundemar and Ny, 1997;Luo and Vincent, 1994;Meffert et al, 1994;Murray, 1997). They have also been reported to be direct inhibitors of lipid peroxidation (Imai et al, 1990;Wong et al, 2000).…”
Section: Heme Oxygenase As Modulator Of Neural Injurymentioning
confidence: 99%
“…High intensity phototherapy (spectral irradiance higher than 30 lW/cm 2 /nm, 430-490 nm band) delivered as close as infants surface is effective in reducing serum unconjugated bilirubin levels and need for exchange transfusion [4]. When compared with conventional phototherapy, LED lights are more effective in reducing serum unconjugated bilirubin levels [18]. In our study all patients were treated with LEDs, low rates of erythrocyte transfusion and no need for exchange transfusions might be due to this new advanced phototherapy method regardless of IVIG.…”
Section: Resultsmentioning
confidence: 99%